If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 14 = x + 2 Reorder the terms: 14 + -2x = x + 2 Reorder the terms: 14 + -2x = 2 + x Solving 14 + -2x = 2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 14 + -2x + -1x = 2 + x + -1x Combine like terms: -2x + -1x = -3x 14 + -3x = 2 + x + -1x Combine like terms: x + -1x = 0 14 + -3x = 2 + 0 14 + -3x = 2 Add '-14' to each side of the equation. 14 + -14 + -3x = 2 + -14 Combine like terms: 14 + -14 = 0 0 + -3x = 2 + -14 -3x = 2 + -14 Combine like terms: 2 + -14 = -12 -3x = -12 Divide each side by '-3'. x = 4 Simplifying x = 4
| x^2+7x+36.75=0 | | 3x-2=20-x | | 4-2c=8 | | -5x-29=145 | | (4x+3)*(3x+2)=0 | | x+6x-1=90 | | (4x-3)*(3x-2)=0 | | 3(2q+3)=5(2q+1) | | -log(x)=20 | | 4x^2+3x+12=12 | | 3(5c-1)-2=13c+13 | | 5x/6-2=3 | | -3x+23=x+3 | | 60x+70y=4200 | | 3(5x-3)-3(2x-5)= | | A-(-3)=25 | | sin(40)=12/x | | y/-9=4 | | x^6-2x^3-4=0 | | 19m+23n+-3n= | | 2x-27=312 | | 7x-19+3x+9=180 | | -(5x-3)-3(2x-5)= | | (4x-6)/3=-2 | | 6*8*18= | | 0.49=cos(x) | | -7(3p+2)40=3(5p+6) | | 18*14*2= | | 5x+32=67 | | N/25-7=-82 | | 3x-2+7+3x-2+7=133 | | -9-5+2-8-9= |